GLUCOSE VARIABILITY AND DIASTOLIC DYSFUNCTION IN PATIENTS WITH TYPE 2 DIABETES - Dzhun, Yana; Mankovsky, Georgy; Rudenko, Nadiya; Marushko, Yevgen; Mankovsky, Borys; Saenko, Yana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Diastolic dysfunction is one of signs of heart failure and could be associated with autonomic neuropathy. Glycemic variability could be one of the reason predisposing to heart failure in subjects with diabetes. We examined the relationship between glycemic variability and diastolic dysfunction in patients with type 2 diabetes mellitus without coronary artery disease. METHODOLOGY Seventy-eight patients with heart failure with preserved left ventricular ejection fraction and type 2 diabetes mellitus were examined. Diastolic function was assessed by echocardiography, glycemic variability was evaluated by continuous glucose monitoring. According to the glycemic variability, all studiypatients were divided into two groups: group I - SD>2 (high glycemic variability), n = 40; group II - SD≤1.9 (normal glycemic variability), n = 38. RESULTS Group I were older (49 (9) vs 46 (5); p<0.05, with a longer duration of DM (10 yrs (9.5) vs 6 yrs(5.5); p<0.01). In group I compared to group II there were more patients with grade 2 diastolic dysfunction (25 (62.5%) vs 10 (26.3), p<0.05). Patients in group I had more severe diastolic dysfunction. In group I patients insulin and sulfonylureas were used more often (11 (27.5%) vs 0 p = 0.0001; 25 (62.5%) vs 10 (26.3%); p<0.01, respectively); patients of group II were more often treated with SGLT2 (2 (5%) vs 13 (34.21%); p<0.01). CONCLUSIONS Increased glycemic variability is associated with diastolic dysfunction and in patients with type 2 diabetes.